2005
DOI: 10.1111/j.1440-1746.2004.03575.x
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophils enhance invasion activity of human cholangiocellular carcinoma and hepatocellular carcinoma cells: An in vitro study

Abstract: The present study suggests the presence of mutual interactions between HuCC-T1/HepG2 carcinoma cells and neutrophils in tumor invasion via paracrine regulation mediated by neutrophil-derived HGF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(36 citation statements)
references
References 20 publications
1
35
0
Order By: Relevance
“…(HGF) from neutrophils, which promoted increased invasiveness by the tumor cells (16). These findings suggest that, although neutrophils release a paucity of cytokine when compared with macrophages and other cells within the tumor microenvironment, the temporal-spatial elaboration of these substances by PMN plays unique roles.…”
Section: Neutrophil-derived Cytokines Participate In Immunosculptingmentioning
confidence: 82%
“…(HGF) from neutrophils, which promoted increased invasiveness by the tumor cells (16). These findings suggest that, although neutrophils release a paucity of cytokine when compared with macrophages and other cells within the tumor microenvironment, the temporal-spatial elaboration of these substances by PMN plays unique roles.…”
Section: Neutrophil-derived Cytokines Participate In Immunosculptingmentioning
confidence: 82%
“…Neutrophils in bronchioloalveolar carcinoma produce hepatocyte growth factor (HGF) that stimulates the migration of the tumor cells [203]. Similarly, human cholangiocellular and hepatocellular carcinoma cells induce HGF secretion by neutrophils, which in turn enhances the invasiveness of the cancer cells [288]. TANs can also stimulate tumor growth by releasing growth factors such as epidermal growth factor, TGFβ and platelet-derived growth factor (PDGF) from the extracellular matrix [289].…”
Section: Neutrophils At the Primary Tumor Sitementioning
confidence: 99%
“…Neutrophils are attracted into lesions by tumor IL-8 production and once in the tumor microenvironment, neutrophils produce many factors that sculpt the tumor [60]. Imai and colleagues observed that neutrophils augment the invasiveness of tumor cells during coculture one effect that was completely blocked by the inclusion of a monoclonal anti-hepatocyte growth factor (HGF) antibody [61]. Subsequent experiments revealed that the tumor cells produced a factor that induced HGF production by the neutrophils, again demonstrating a mutually beneficial interaction between tumor and immune effect.…”
Section: C121 Immune Effectors Can Simultaneously Sculpt Tumors Fmentioning
confidence: 99%